Effects of legume intercrops on soilborne pests, biomass, nutrients, and soil water in banana - McIntyre, B.D.; Gold, Cliford S.; Kashaija, I.N.; Ssali, H.; Night, G.; Bwamiki, D.P. (Springer, 2001)
Banana (Musa AAA) and plantain (Musa AAB) are important dietary staples for over 70 million people in sub-Saharan Africa. Banana weevil (Cosmopolites sordidus) and nematodes (Radopholus similis, Helicotylenchus multicinctus) are often the largest constraints to production. Leguminous crops in the genera Canavalia, Mucuna and Tephrosia have been reported as having repellent or insecticidal properties. We assessed: weevil and nematode populations and damage; banana growth and development; soil and foliar nutrient concentrations; and soil moisture status in banana intercropped with three legumes (Canavalia ensiformis, Mucuna pruriens and Tephrosia vogelii). The research took place at Kawanda, Uganda, on a field site infested with weevils and nematodes. The legume intercrops did not affect weevil populations or damage. The legumes also provided no benefit in terms of nematode control; in fact, banana root necrosis was higher in the T. vogelii intercrop than in the banana monoculture. Banana fruit yield was not adversely affected by the legume intercrops. The low yield noted across treatments was attributed to the high level of damage by the weevils and the nematodes. Significantly more NO3-N accumulated from 0- to 0.3-m depth in the M. pruriens intercrop than in the other treatments. There was no treatment difference in soil moisture. In summary, there was no significant advantage in banana production associated with the legume intercrops. However, the lack of a significant difference in banana fruit production between the monoculture and the intercrops suggests that land use efficiency may be increased by incorporating food and or/fodder legumes into the banana cropping system.